Emotional Labor, Occupational Burnout and Job Satisfaction – The Moderating Role of the Service Sector (Commercial Versus Social) - Finogenow, Maria (Przegląd Psychologiczny, 2025)
Objective: The main objective of the study was to examine whether there are associations between emotional labor and occupational burnout and job satisfaction, as well as to determine whether the service sector (commercial and social) serves as a moderator of these relationships. The study also aimed to assess whether employees in the commercial services sector differ from those in the social services sector in the intensity of emotional labor, occupational burnout, and job satisfaction. Method: The study included 150 participants, of whom 77 were employees from the commercial services sector and 78 were employees from the social services sector. To measure the variables, the Surface Acting and Deep Acting Scale, the Maslach Burnout Inventory – General Survey, the Job Satisfaction Scale, and the Work Affect Scale were used. Comparative analyses, correlation analyses, and regression analyses with interaction terms were conducted using Hayes’ PROCESS macro. Results: Employees in commercial services significantly more often perform surface acting in the form of faking emotions than employees in social services. The associations between emotional labor and its consequences pertain mainly to surface acting and are mostly significant only among employees in social professions. Conclusion: The profession performed, classified within the commercial versus social services sector, may serve as a moderator of the relationships between emotional labor and its consequences.